Ultraviolet Radiation Stimulates Activity of CO2 Concentrating Mechanisms in a Bloom-Forming Diatom Under Reduced CO2 Availability - Gao, Guang; Liu, Wei; Zhao, Xin; Gao, Kunshan (Frontiers in Microbiology, 2021)
The diatom Skeletonema costatum is cosmopolitan and forms algal blooms in coastal waters, being exposed to varying levels of solar ultraviolet radiation (UVR) and reduced levels of CO2. While reduced CO2 availability is known to enhance CO2 concentrating mechanisms (CCMs) in this diatom and others, little is known on the effects of UV on microalgal CCMs, especially when CO2 levels fluctuate in coastal waters. Here, we show that S. costatum up-regulated its CCMs in response to UVR (295–395 nm), especially to UVA (320–395 nm) in the presence and absence of photosynthetically active radiation (PAR). UVA and/or UVR alone energized the increase of the activity of extracellular carbonic anhydrase (CAe). The addition of UVA enhanced the activity of CCMs-related CAe by 23–27% when PAR levels were low. Such UVA-stimulated CCMs activity was only significant at the reduced CO2 level (3.4 μmol L-1). In addition, UVA alone drove active HCO3- uptake, another evidence for its role in enhancing CCMs activity. In parallel, presence of UVA enhanced photosynthetic carbon fixation only at the lower CO2 level. Regardless of the CO2 levels, carbon fixation increased linearly with increased intensities of UVA or UVR alone. These findings imply that during S. costatum blooming period when CO2 and PAR availability becomes lower, solar UV radiation (mainly UVA) helps to upregulate its CCMs and thus carbon fixation, enabling its success of frequent algal blooms.